FEATURES OF THE DEVELOPMENT OF PHYSICAL EDUCATION TOOLS IN STUDENTS - Yormatov Ghulom (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on the means of physical education for school-aged children and systematic physical exercises, mainly on developing children’s strength, strengthening their elasticity, improving breathing, blood circulation and heart system work, and metabolism in organs.